Identification of Hic–5 as a Novel Scaffold for the MKK4/p54 JNK Pathway in the Development of Abdominal Aortic Aneurysms. Issue 3 (8th May 2014) - Lei, Xiao‐Feng; Kim‐Kaneyama, Joo‐ri; Arita‐Okubo, Shigeko; Offermanns, Stefan; Itabe, Hiroyuki; Miyazaki, Takuro; Miyazaki, Akira
Abstract : Background: Although increased amounts of reactive oxygen species in the pathogenesis of abdominal aortic aneurysm (AAA) are well documented, the precise molecular mechanisms by which reactive oxygen species induce AAAs have not been fully elucidated. This study focused on the role of hydrogen peroxide–inducible clone 5 (Hic‐5), which is induced by hydrogen peroxide and transforming growth factor‐β, in the cellular signaling of AAA pathogenesis. Methods and Results: Using the angiotensin II–induced AAA model in Apoe −/− mice, we showed that Apoe −/− Hic‐5 −/− mice were completely protected from AAA formation and aortic rupture, whereas Apoe −/− mice were not. These features were similarly observed in smooth muscle cell–specific Hic‐5–deficient mice. Furthermore, angiotensin II treatment induced Hic‐5 expression in a reactive oxygen species–dependent manner in aortic smooth muscle cells in the early stage of AAA development. Mechanistic studies revealed that Hic‐5 interacted specifically with c‐Jun N‐terminal kinase p54 and its upstream regulatory molecule mitogen‐activated protein kinase kinase 4 as a novel scaffold protein, resulting in the expression of membrane type 1 matrix metalloproteinase and matrix metalloproteinase 2 activation in aortic smooth muscle cells. Conclusion: Hic‐5 serves as a novel scaffold protein that specifically activates the mitogen‐activated protein kinase kinase 4/p54 c‐Jun N‐terminal kinase pathway, thereby leading to the induction and activation of matrix metalloproteinases in smooth muscle cells and subsequent AAA formation. Our study provided a novel therapeutic option aimed at inhibiting the mitogen‐activated protein kinase kinase 4–Hic‐5–p54 c‐Jun N‐terminal kinase pathway in the vessel wall, particularly through Hic‐5 inhibition, which may be used to produce more precise and effective therapies.